Urethral Pressure Measurement as a Tool for the Urodynamic Diagnosis of Detrusor Sphincter Dyssynergia - Corona, Lauren E. (Int Neurourol J, 2018)
PURPOSE: To describe a technique for urodynamic diagnosis of detrusor sphincter dyssynergia (DSD) using urethral pressure measurements and examine potential associations between urethral pressure and bladder physiology among patients with DSD. METHODS: Multiple sclerosis (MS) and spinal cord injured (SCI) patients with known DSD diagnosed on videourodynamics (via electromyography or voiding cystourethrography) were retrospectively identified. Data from SCI and MS patients with detrusor overactivity (DO) without DSD were abstracted as control group. Urodynamics tracings were reviewed and urethral pressure DSD was defined based on comparison of DSD and control groups. RESULTS: Seventy-two patients with DSD were identified. Sixty-two (86%) had >20 cm H(2)O urethral pressure amplitude during detrusor contraction. By comparison, 5 of 23 (22%) of control group had amplitude of >20 cm H(2)O during episode of DO. Mean duration of urethral pressure DSD episode was 66 seconds (range, 10–500 seconds) and mean urethral pressure amplitude was 73 cm H(2)O (range, 1–256 cm H(2)O). Longer (>30 seconds) DSD episodes were significantly associated with male sex (81% vs. 50%, P=0.013) and higher bladder capacity (389 mL vs. 219 mL, P=0.0004). Urethral pressure amplitude measurements during DSD were not associated with significant urodynamic variables or neurologic pathology. CONCLUSIONS: Urethral pressure amplitude of >20 cm H(2)O during detrusor contraction occurred in 86% of patients with known DSD. Longer DSD episodes were associated with larger bladder capacity. Further studies exploring the relationship between urethral pressure measurements and bladder physiology could phenotype DSD as a measurable variable rather than a categorical observation.